Rodzicielstwo jako wymiar biografii rodzinnej – implikacje badawcze - Kuryś-Szyncel, Karolina (Studia Edukacyjne, 2025)
The article attempts to view parenthood as one of the dimensions of family biography, which determines the dynamics of the family system, both in the developmental and semantic layers. By systemic and biographical perspective author indicated a new, in pedagogical science, category of family biography, which is understood as multiplied (being more than the sum of individual biographies), subject to systemic rules of circularity and equipotentiality, endless reconstruction resulting from the tension between the course of family life and the story about the history of life. Recognition of the family as a dynamic and learning system enables the use of qualitative methods to study selected areas and topics of family life and diverse family structures. In this approach, parenthood is a dimension that constitutes the biography of the family system and is subject to research. Parenting is understood, on the one hand, as a biographical solution for a system that is subject to a dynamic equilibrium of tensions, and on the other hand, as a functional dimension of the family (along with cohesion, flexibility and communication). The author indicates the possibilities of qualitative research on the family system with the use of narrative and biographical methods.